2021
DOI: 10.1016/j.jcmgh.2020.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Tristetraprolin Promotes Hepatic Inflammation and Tumor Initiation but Restrains Cancer Progression to Malignancy

Abstract: Background & Aims Tristetraprolin (TTP) is a key post-transcriptional regulator of inflammatory and oncogenic transcripts. Accordingly, TTP was reported to act as a tumor suppressor in specific cancers. Herein, we investigated how TTP contributes to the development of liver inflammation and fibrosis, which are key drivers of hepatocarcinogenesis, as well as to the onset and progression of hepatocellular carcinoma (HCC). Methods TTP expression was investigated in mouse/h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 72 publications
0
13
0
Order By: Relevance
“…We previously reported such discrepant results for another important post-transcriptional regulator, which acts similarly to a miRNA, i.e., the RNA-binding protein tristetraprolin (TTP). In vivo studies using TTP knockout mice indicated an oncogenic function for this protein in HCC development, whereas TTP appeared to have a tumor-suppressive role in hepatic cultured cancer cells [ 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported such discrepant results for another important post-transcriptional regulator, which acts similarly to a miRNA, i.e., the RNA-binding protein tristetraprolin (TTP). In vivo studies using TTP knockout mice indicated an oncogenic function for this protein in HCC development, whereas TTP appeared to have a tumor-suppressive role in hepatic cultured cancer cells [ 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, suppression of TTP phosphorylation by MK2 inhibitor was shown to impair TTP activity in HCC cell lines [130], whereas TTP ability to regulate c-Myc was abrogated by methylation of a single CpG site in its promoter [131]. We also recently showed that the TTP expression is regulated by the HNF4α/EGR1 axis in Huh7 cells [125]. Although the precise role and functions of TTP in liver diseases and HCC have started to be delineated, whether TTP regulates SGs biogenesis or requires these entities for its functions, as suggested in non-hepatic cell lines [127], remains to be investigated in the liver.…”
Section: Ttpmentioning
confidence: 94%
“…eIF4E2) -GYF2 (GRB10-interacting GYF protein 2) cap-binding complex, and a Not-1 binding domain [120][121][122]. It is usually described as a tumor suppressor, downregulated in many human cancers, and its level correlates with a poor clinical outcome [123][124][125]. TTP binds to mRNA transcripts and targets them for degradation in P-bodies.…”
Section: Ttpmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, lower level of TTP is related to more aggressive phenotype in HCC. Loss of TTP will show high correlation with late-stage, high-grade of HCC (23,24). Therefore, TTP could be considered a tumor suppressor in most cancers, and upregulating TTP expression might help improve prognosis.…”
Section: Roles Of Ttp In Carcinomamentioning
confidence: 99%